A Systematic Review of the Research Models of Brands Subject Doctoral Theses Published in 2020-2023 at the YÖK National Thesis Center - Reha Saydan; Zübeyir Çelik (Yüzüncü Yıl Üniversitesi Sosyal Bilimler Enstitüsü Dergisi, 2024)
The aim of this study is to examine the research models of doctoral theses published on brands subject in 2020-2023. For this aim, the content analysis of the doctoral theses retrieved from the database of the YÖK National Thesis Centre was carried out using PRISMA 2009 Flow Diagram. Secondary data sources obtained from 85 doctoral theses evaluated were analyzed using VOSviewer and UCINET programs. As a result of the analyses, a total of 40 brand concepts were evaluated in the research models of doctoral theses published on brand concepts. It can be seen that some similar brand concepts have been evaluated in the research models of relevant theses in all years. Brand loyalty, brand equity, brand image, brand quality, brand trust, brand satisfaction, brand experience, brand awareness, brand attitude and brand love are the common motor structures with high link strength that are evaluated in most of the dissertations. However, the concepts of brand loyalty, brand trust, brand quality, brand equity and brand image, which have a higher number of direct ties and eigenvector values, are the leading actors. The results of the study are discussed and implications are provided.